Role of the Central Cholinergic Nervous System in Motor and Non-Motor Symptoms of Parkinson’s Disease - Tian, Si-Yuan; Cao, Xin; Liu, Guo-Jin; Zi, Ying; Zhu, Hui-Xian; Jiang, Yi-Miao; Lou, Wei-Wei; Fang, Xiao-Xia; Shan, Ling; Liu, Zhan; Zhuang, Qian-Xing (Current Neuropharmacology, 2025)
Parkinson’s disease (PD) is a prevalent neurodegenerative disorder that is characterized by both motor and non-motor symptoms. Although dopamine agonists have been demonstrated to be efficacious in the treatment of motor symptoms, their capacity to enhance non-motor symptoms remains constrained. This suggests that additional neurotransmitter systems may be involved in the pathogenesis of PD-related symptoms. The cholinergic nervous system plays a pivotal role in the central nervous system, with various projection systems associated with diverse functions, including but not limited to learning, memory, attention, posture, balance, eye movement control, and adaptation. Nevertheless, the role of the cholinergic nervous system in the motor and non-motor impairments associated with PD remains uncertain. This review elucidates the location, projection, receptors, and effects of central cholinergic systems, as well as their role in both the motor symptoms and non-motor symptoms of PD. Additionally, it examines the crosstalk between cholinergic systems and dopaminergic systems in PD pathology. A deeper comprehension of the fundamental mechanisms of the cholinergic system in PD may facilitate the development of novel therapeutic strategies.
Keywords: cholinergic system